EFEKTIVITAS PEMBELAJARAN PENJAS MENGGUNAKANAUDIO VISUAL TERHADAP MOTIVASI DAN HASIL BELAJARANAK TUNAGRAHITA RINGAN PADA MASA PANDEMI (COVID19) DI SLB PAGADEN SUBANG - Fauzia Agung Lestari, - (2023)
ABSTRACT THE EFFECTIVENESS OF PENJAS LEARNING USING AUDIO VISUAL ON THE MOTIVATION AND LEARNING OUTCOMES OF MIDDLE TENDER CHILDREN DURING THE PANDEMIC (COVID19) PERIOD AT SLB PAGADEN SUBANG Fauzia Agung Lestari E-mail:fagunglestari@gmail.com Pembimbing 1 : Prof. Dr. Beltasar Tarigan, MS, AIFO. Pembimbing 2 : Dr. Reshandi Nugraha, M. Pd. The purpose of this study was to find out how the effectiveness of Physical Education learning using Adio Visual has on the motivation and learning outcomes of mildly mentally retarded children and to find out the problems experienced by teachers during the Covid-19 pandemic at SLB Pagaden Subang. This study used a quantitative method with a one group pretest and posttest design. The research population for SLB Tarbiyatul Mutaalimin Pagaden Subang, the sample used in this study consisted of 15 students with mild mental retardation and 1 teacher. The instruments used are questionnaires, observations and documentation. The results showed that the SPSS test using the paired samples statistical test phase average pretest value was 40.03 <49.30, so that means there was an increase in the average motivation and student learning outcomes. Testing paired samples correlation found a correlation coefficient of 0.124 with a significant value of 0.515, because the sig. 0.515 > 0.05, it can be said that there is a relationship between the pretest variables and the posttest variables. Testing the paired samples t test found that the sig (2-tailed) value of 0.000 was less than 0.05, then HO was rejected and Ha was accepted. Thus the use of Audio Visual learning media has an effect on increasing motivation and student learning outcomes. Keywords: Covid-19 Pandemic, Audio-Visual, Motivation, Learning Outcomes, Special Schools